Entrepreneurship processes in Colombia and their impact on the productive sectors - Lopez-Rodriguez, Campo Elias (Ediciones UNL. Secretaría de Extensión de la UNL, 2021)
Entrepreneurship is a wealth-generating activity since knowledge, creativity and innovation of entrepreneurial ideas will benefit society and, in turn, the productive sector. Through a review of the literature, the evolu-tion of entrepreneurial processes in Colombia and their impact on the country’s productive sectors are recognized. It is evident that the sector with the smallest stock of companies is the construction sector and the one with the highest level is the commercial sector; the services sector is the one with the highest volatility, while the industrial sector is the moststatic. The services sector is experiencing a gradual decline compared to the development of future ventures, with consumption being the key sector in terms of business creation for the Colombian context.